Caretakers' Role in Personal Hygiene Children with Down Syndrome - Purnamawati, Rifka; Shaluhiyah, Zahroh; Suryoputro, Antono (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Despite their flaws, children with down syndrome require caretakers' involvement, especially in personal hygiene. Caretakers play a critical role in meetings in terms of cleanliness. This study investigates the role of caretakers in the Personal Hygiene of children with down syndrome. Subjects and Method: This study was a qualitative phenomenological approach conducted at Public Disability-Specific Schools in Semarang, Central Java, Indonesia. Purposive sampling of 10 people based on specific criteria is used to find participants. In-depth interviews, observations, and field notes were used to collect data. Results: This study has resulted that the role of caretakers in the personal hygiene of children with down syndrome is divided into five themes: developing communication skills with children, providing examples through specific media, providing surrounding support, providing a reward or consequences, and modeling. Conclusion: The role of caretakers has a significant impact on the learning of personal hygiene, so strategies are required to enable children to carry out self-cleaning tasks thoroughly. Keywords: caretaker; personal hygiene; down syndrome. Correspondence:Rifka Purnamawati. Master’s Program in Health Promotion, Diponegoro University, Indonesia. Email: rifka_purnamawati@yahoo.com. Mobile: +6287836126783.